Antimicrobial Activity of Spices Popularly Used in Mexico against Urinary Tract Infections - Ariadna Jazmín Ortega-Lozano; Estefani Yaquelin Hernández-Cruz; Tania Gómez-Sierra; José Pedraza-Chaverri (MDPI AG, 2023)
Urinary tract infections (UTIs) are the most common infectious diseases worldwide. These infections are common in all people; however, they are more prevalent in women than in men. The main microorganism that causes 80-90% of UTIs is Escherichia coli. However, other bacteria such as Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa, Proteus mirabilis, and Klebsiella pneumoniae cause UTIs, and antibiotics are required to treat them. However, UTI treatment can be complicated by antibiotic resistance and biofilm formation. Therefore, medicinal plants, such as spices generally added to foods, can be a therapeutic alternative due to the variety of phytochemicals such as polyphenols, saponins, alkaloids, and terpenes present in their extracts that exert antimicrobial activity. Essential oils extracted from spices have been used to demonstrate their antimicrobial efficacy against strains of pathogens isolated from UTI patients and their synergistic effect with antibiotics. This article summarizes relevant findings on the antimicrobial activity of cinnamon, clove, cumin, oregano, pepper, and rosemary, spices popularly used in Mexico against the uropathogens responsible for UTIs.